2019
DOI: 10.1016/j.jcte.2019.100192
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic dysfunction in Emirati subjects in Abu Dhabi: Relationship to levels of soluble RAGEs

Abstract: Highlights In Abu Dhabi, sRAGE levels were significantly lower in T2D vs. control subjects. There were no significant differences in esRAGE levels in T2D vs. control subjects. Levels of sRAGE in T2D vs. controls were not significant after correction for eGFR. In T2D subjects ≥age 70 years, trends to lower eGFR were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This showed that hyperglycemia in diabetes mellitus triggered the production of AGEs in the serum and a decrease in sRAGE. This study is consistent with previous findings that AGEs increased in T2DM, while sRAGE decreased (Abdulle et al, 2019).The formation of AGEs in bone matrix will increase the rate of apoptosis of osteoblasts and its precursor cells (Picke et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This showed that hyperglycemia in diabetes mellitus triggered the production of AGEs in the serum and a decrease in sRAGE. This study is consistent with previous findings that AGEs increased in T2DM, while sRAGE decreased (Abdulle et al, 2019).The formation of AGEs in bone matrix will increase the rate of apoptosis of osteoblasts and its precursor cells (Picke et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…The sRAGE circulates in the plasma naturally and represent as an enticement to inhibit the binding of AGEs-RAGE (Devangelio et al, 2007). The T2DM patients had significantly lower levels of plasma sRAGE than control (Abdulle et al, 2019). The diabetes animal model also demonstrated a decrease of sRAGE levels (Hsia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, elevated serum AGEs levels are still to be correlated to the development of specific complications. Serum AGEs and sRAGE levels were not related to vascular complications in patients with prediabetes nor impaired glucose metabolism in patients with type 2 diabetes [78,79]. Although in higher levels, CML and sRAGE were also not associated with obesity or inflammation in unhealthy obese adolescents [80].…”
Section: Evidence In Human Studiesmentioning
confidence: 84%